(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Temaja IGRM, Selangga DGW, Sudiarta IP, Listhiani L. 2024. Antiviral activity of Eucheuma cottonii to control Pepper yellow leaf curl virus. Biodiversitas 25: 1615-1622. The chili pepper plant in Bali is often infected with yellow curl symptoms caused by Pepper yellow leaf curl Indonesia virus (PYLCIV). The virus is always present in the field and no control measure has been found effective to suppress the PYLCIV infection. Control efforts using macroalgae extract have been frequently used and are able to suppress plant virus infection, but no report on its effectiveness in suppressing PYLCIV infection. This research aimed to analyze the effect of Eucheuma cottonii Weber Bosse macroalgae extract in suppressing PYLCIV infection on chili pepper plants in Bali. The observed parameters were symptom changes, disease incidence and severity, virus confirmation by PCR, and phytochemical analysis. Chili pepper plants infected by PYLCIV before E. cottonii application showed moderate to severe symptoms, but after E. cottonii application plants turned symptomless or showed light symptoms. The PYLCIV disease incidence in chili pepper Seret and Pelita8 cultivars before application was 100%, and after application ranged from 45-55%. The PYLCIV disease severity in chili pepper Seret and Pelita 8 cultivars before application ranged between 68-72%, and after application ranged between 25-34%. PYLCV on chili pepper Seret and Pelita 8 cultivar that were treated with E. cottonii produced lighter DNA band compared to positive control (C+). Major compounds found in E. cottonii extract were propanoic acid, ethyl ester; n-propyl acetate; sec-Butyl acetate; Toluene; Bicyclo [4.2.0] octa-1, 3, 5- triene; and styrene. The E. cottonii extract was able to suppress the PYLCIV infection on chili pepper plants.